The impact of demographic disparities in the presentation of sarcoidosis: A multicenter prospective study. (October 2021) - Zhou, Ying; Gerke, Alicia K.; Lower, Elyse E.; Vizel, Alexander; Talwar, Deepak; Strambu, Irina; Francesqui, Joel; Sellares, Jacobo; Sawahata, Michiru; Obi, Ogugua Ndili; Nagai, Sonoko; Tanizawa, Kiminobu; et al.
Abstract: Objective: To study how demographic differences impact disease manifestation of sarcoidosis using the WASOG tool in a large multicentric study. Methods: Clinical data regarding 1445 patients with sarcoidosis from 14 clinical sites in 10 countries were prospectively reviewed from Feb 1, 2020 to Sep 30, 2020. Organ involvement was evaluated for the whole group and for subgroups differentiated by sex, race, and age. Results: The median age of the patients at diagnosis was 46 years old; 60.8% of the patients were female. The most commonly involved organ was lung (96%), followed by skin (24%) and eye (22%). Black patients had more multiple organ involvement than White patients (OR = 3.227, 95% CI: 2.243–4.643) and females had more multiple organ involvement than males (OR = 1.238, 95% CI: 1.083–1.415). Black patients had more frequent involvement of neurologic, skin, eye, extra thoracic lymph node, liver and spleen than White and Asian patients. Women were more likely to have eye (OR = 1.522, 95%CI: 1.259–1.838) or skin involvement (OR = 1.369, 95%CI: 1.152–1.628). Men were more likely to have cardiac involvement (OR = 1.326, 95%CI: 1.096–1.605). A total of 262 (18.1%) patients did not receive systemic treatment for sarcoidosis. Therapy was more common in Black patients than in other races. Conclusion: The initial presentation and treatment of sarcoidosis was related to sex, race, and age. Black and female individuals are found to have multiple organ involvement more frequently. Age at diagnosis<45, Black patients and multiple organ involvement were independent predictors of treatment. Highlights: It is an international study with large cohort of patients with sarcoidosis. Organ involvement and treatment differed according to race, sex, and age. Black and female individuals were more likely to have multiple organ involvement. Age at diagnosis<45, Black patients and multiple organ involvement were independent predictors of treatment.